Tombs, trowels and treasures : the first 40 years of Egyptology at Macquarie University - Binder, Susanne, 1958-; Donovan, Leonie, (Studies (Australian Centre for Egyptology), 2018)
To celebrate 40 years of Egyptology at Macquarie University, 'Tombs, Trowels and Treasures' provides an overview of the fieldwork undertaken in Egypt from the early days until the present and records our engagement in teaching, research and community outreach. Part One presents the fieldwork projects conducted by Macquarie in over 20 sites and 80 tombs. The projects are arranged by site in the chronological order in which the work was undertaken. The special, unusual and sometimes unique scenes and finds are showcased in over 650 photographs. Part Two has three sections reflecting the distinct areas of our engagement in teaching Egyptology in the Department of Ancient History, with research in Egyptology at Macquarie University through The Australian Centre for Egyptology, as well as our multi-facetted commitment to making Egyptology accessible to the wider community through The Rundle Foundation for Egyptian Archaeology.